Invasive Electrophysiology for Circuit Discovery and Study of Comorbid Psychiatric Disorders in Patients With Epilepsy: Challenges, Opportunities, and Novel Technologies - Balzekas, Irena; Sladky, Vladimir; Nejedly, Petr; Brinkmann, Benjamin H.; Crepeau, Daniel; Mivalt, Filip; Gregg, Nicholas M.; Pal Attia, Tal; Marks, Victoria S.; Wheeler, Lydia; Riccelli, Tori E.; Staab, Jeffrey P.; et al. (Frontiers in Human Neuroscience, 2021)
Intracranial electroencephalographic (iEEG) recordings from patients with epilepsy provide distinct opportunities and novel data for the study of co-occurring psychiatric disorders. Comorbid psychiatric disorders are very common in drug resistant epilepsy and their added complexity warrants careful consideration. In this review, we first discuss psychiatric comorbidities and symptoms in patients with epilepsy. We describe how epilepsy can potentially impact patient presentation and how these factors can be addressed in the experimental designs of studies focused on the electrophysiologic correlates of mood. Second, we review emerging technologies to integrate long-term iEEG recording with dense behavioral tracking in naturalistic environments. Third, we explore questions on how best to address the intersection between epilepsy and psychiatric comorbidities. Advances in ambulatory iEEG and long-term behavioral monitoring technologies will be instrumental for studying the intersection of seizures, epilepsy, psychiatric comorbidities, and their underlying circuitry.